Pharmacokinetics of Oral and Inhaled Terbutaline after Exercise in Trained Men - Dyreborg, Anders; Krogh, Nanna; Backer, Vibeke; Rzeppa, Sebastian; Hemmersbach, Peter; Hostrup, Morten (Frontiers in Pharmacology, 2016)
Aim: The aim of the study was to investigate pharmacokinetics of terbutaline after oral and inhaled administration in healthy trained male subjects in relation to doping control. Methods: Twelve healthy well-trained young men (27 ±2 years; mean ± SE) underwent two pharmacokinetic trials that compared 10 mg oral terbutaline with 4 mg inhaled dry powder terbutaline. During each trial, subjects performed 90 min of bike ergometer exercise at 65% of maximal oxygen consumption. Blood (0–4 h) and urine (0–24 h) samples were collected before and after administration of terbutaline. Samples were analyzed for concentrations of terbutaline by high performance liquid chromatography coupled to tandem mass spectrometry (HPLC-MS/MS). Results: Pharmacokinetics differed between the two routes of administration. Serum Cmax and area under the serum concentration-time curve (AUC) were lower after oral administration compared to inhalation (Cmax: 4.2 ± 0.3 vs. 8.5 ± 0.7 ng/ml, P ≤ 0.001; AUC: 422 ± 22 vs. 1308 ± 119 ng/ml × min). Urine concentrations (sum of the free drug and the glucuronide) were lower after oral administration compared to inhalation 2 h (1100 ± 204 vs. 61 ± 10 ng/ml, P ≤ 0.05) and 4 h (734 ± 110 vs. 340 ± 48 ng/ml, P ≤ 0.001) following administration, whereas concentrations were higher for oral administration than inhalation 12 h following administration (190 ± 41 vs. 399 ± 108 ng/ml, P ≤ 0.05). Urine excretion rate was lower after oral administration than inhalation the first 2 h following administration (P ≤ 0.001). Systemic bioavailability ratio between the two routes of administration was 3.8:1 (inhaled: oral; P ≤ 0.001). Conclusion: Given the higher systemic bioavailability of inhaled terbutaline compared to oral, our results indicate that it is difficult to differentiate allowed inhaled use of terbutaline from prohibited oral ingestion based on urine concentrations in doping control analysis. However given the potential performance enhancing effect of high dose terbutaline, it is essential to establish a limit on the WADA doping list.